Pengolahan Dan Analisis Usaha Tanaman Jahe Menjadi Produk Jahe Instan Di Panti Asuhan Al-Ikhlas Ngentak Pelem RT.13 Baturetno Banguntapan Bantul - Nurcahyani Dewi Retnowati; Daru Retnowati (Institut Teknologi Dirgantara Adisutjipto, 2019)
Ginger plants are widely cultivated in Indonesia and can be used for health. One of the ginger products is instant ginger. The process of making instant ginger can be easily done by everyone, especially the children of the orphanage. The aim of community service is that children of Orphanage are expected to make their own instant ginger, sell, and do business analysis calculations so that the children of the Orphanage become more independent. The training process for making instant ginger and business analysis was carried out at the Al-Ikhlas Orphanage Ngentak Pelem RT.13 Baturetno Banguntapan Bantul Yogyakarta. The method carried out in the implementation of this training was by counseling and practicing directly the making of instant ginger and calculation of business analysis. There are three types of activities, namely an explanation of ginger plants and their properties, making instant ginger products, and teaching business analysis calculations and a little about product marketing. The output target to be achieved in this community service is that the partners are able to make instant ginger and business analysis.